An ALS-Associated Mutant SOD1 Rapidly Suppresses KCNT1 (Slack) Na(+)-Activated K(+) Channels in Aplysia Neurons - Zhang, Yalan (J Neurosci, 2017)
Mutations that alter levels of Slack (KCNT1) Na(+)-activated K(+) current produce devastating effects on neuronal development and neuronal function. We now find that Slack currents are rapidly suppressed by oligomers of mutant human Cu/Zn superoxide dismutase 1 (SOD1), which are associated with motor neuron toxicity in an inherited form of amyotrophic lateral sclerosis (ALS). We recorded from bag cell neurons of Aplysia californica, a model system to study neuronal excitability. We found that injection of fluorescent wild-type SOD1 (wt SOD1YFP) or monomeric mutant G85R SOD1YFP had no effect on net ionic currents measured under voltage clamp. In contrast, outward potassium currents were significantly reduced by microinjection of mutant G85R SOD1YFP that had been preincubated at 37°C or of cross-linked dimers of G85R SOD1YFP. Reduction of potassium current was also seen with multimeric G85R SOD1YFP of ∼300 kDa or >300 kDa that had been cross-linked. In current clamp recordings, microinjection of cross-linked 300 kDa increased excitability by depolarizing the resting membrane potential, and decreasing the latency of action potentials triggered by depolarization. The effect of cross-linked 300 kDa on potassium current was reduced by removing Na(+) from the bath solution, or by knocking down levels of Slack using siRNA. It was also prevented by pharmacological inhibition of ASK1 (apoptosis signal-regulating kinase 1) or of c-Jun N-terminal kinase, but not by an inhibitor of p38 mitogen-activated protein kinase. These results suggest that soluble mutant SOD1 oligomers rapidly trigger a kinase pathway that regulates the activity of Na(+)-activated K(+) channels in neurons. SIGNIFICANCE STATEMENT Slack Na(+)-activated K(+) channels (KCNT1, K(Na)1.1) regulate neuronal excitability but are also linked to cytoplasmic signaling pathways that control neuronal protein translation. Mutations that alter the amplitude of these currents have devastating effects on neuronal development and function. We find that injection of oligomers of mutant superoxide dismutase 1 (SOD1) into the cytoplasm of invertebrate neurons rapidly suppresses these Na(+)-activated K(+) currents and that this effect is mediated by a MAP kinase cascade, including ASK1 and c-Jun N-terminal kinase. Because amyotrophic lateral sclerosis is a fatal adult-onset neurodegenerative disease produced by mutations in SOD1 that cause the enzyme to form toxic oligomers, our findings suggest that suppression of Slack channels may be an early step in the progression of the disease.